The Implementation of Profit Sharing on Fathonah Education Savings Products at BMT NU Kapongan Situbondo Branch, East Java, Indonesia - May Shinta Retnowati; Fadhila Sukur Indra; Yeni Zannuba Arifah; Devid Frastiawan Amir Sup (JOURNAL OF SHARIA ECONOMICS, 2022)
Baitul Maal wa Tamwil (BMT) is a form of simple Islamic financial institution. BMT in its operational system carries out business and social activities. BMT NU Kapongan Situbondo branch is one of the BMT institutions, the application of its activities to the business sector (tamwil) can be in the form of savings or deposits and also financing activities are always based on sharia compliance, especially in funding or deposit activities at BMT NU Kapongan Situbondo branch. As for the profit sharing that will be obtained by the customer in the form of automatic money, the customer does not know for sure the amount of profit obtained from the contract. This study aims to analyze the implementation and determination of profit sharing in the mudharabah muthlaqah contract in the fathonah education savings product of BMT NU Kapongan Situbondo branch. The research method used in this study is a qualitative descriptive method. The results of the study explain that the implementation of fathonah education savings is in accordance with sharia principles in terms of fulfillment rather than contracts, this can be proven by the owner of capital giving freedom to mudharib (BMT). However, the distribution of the profit sharing ratio is not fixed because there are several things, including the small number of customers who collect their funds in fathonah education savings products and the small profit income from managed capital, causing the context of determining the profit sharing ratio not in accordance with the specified contract.